Livestocks systems with tropical dairy creolle (Reyna) in Costa Rica. - Vilaboa Arroniz, Julio (2012)
The aim of this study was to identify the technology components used in livestock systems withTropical Dairy Creole (CLT) Reyna and socioeconomic characteristics of farmers who use this race. The study was conducted in the provinces of Cartago and Guanacaste, Costa Rica in May-July 2011. We interviewed managers of dairy modules at Experiment Station Alfredo Volio Mata(EEAVM) at the University of Costa Rica and the Tropical Agricultural Research and Education (CATIE) plus fi veindependent producers. Variables analyzed were social, technological and commercial awareness as well as the useof this breed. The data was analyzed by descriptive statistics and cluster analysis using SAS version 8.0. There were four groups called G1: Guanacaste producers, G2: EEAVM,G3: Cartago producer and G4: CATIE. The surface forthese groups was 60±31.6, 24, 57 and 46 hectares with aunited animal per hectare (AU ha-1) 0.6±0.1, 2.6, 0.7 and4.1, respectively. Race Reyna is mainly used to establish Bos taurus and/or Bos indicus crosses in order to obtain adaptability and resistance to the environment. However, itsuse and management has been undermined by institutional policies, both legal and productive.